Perception of Breastfeeding among Female Medical Students, Taibah University, Medina, Saudi Arabia 2012 - Aziz, Ghaida; jabri, Ghaida; Al-Ahmadi, Ghaida; Ehab, Mona; khaled, Marwa; Hafiz, Asma’a; Hadi, Hadeel (Journal of medical and pharmaceutical sciences, 2017)
Breast feeding (BF) is known to have many advantages but our Arab region has a pattern similar to western countries; where exclusive breastfeeding less than 35%. Knowledge given to women during her antenatal visits plays an important influential role in her attitude and practice of BF later on. Objective: To explore knowledge and attitude of female medical students at Taibah University about breastfeeding. Methods: A Cross sectional study was carried out from October to November 2012. It included female medical students. Stratified sampling allocation technique was used; with a total sample of 149 students. A specialty designed self-administrated questionnaire in Arabic form was used. It included socio-demographic data, obstetric history, data about the knowledge and attitude of female medical students towards breastfeeding value and guidelines. Mean percent knowledge score for value of BF, mean percent score for BF guidelines and mean percent score for attitude were calculated. Appropriate statistical tests for qualitative and quantitative data were used accordingly. Results: Majority (91.9%) (of the studied sample) was never married and 37.6% got their knowledge about BF via books. Regarding ever married women, 58.3% only were gravid (mean =2.2±1.94). Only 25.0% were family planning users; 66.7% of them used hormonal contraceptives. Only 20% breast fed their infants with a mean duration for exclusive BF of 3.8 ± 2.87 months and mean age of weaning of 2.3 ±0.63 months. The mean knowledge percent score for guidelines of BF was 64.7±8.45. The mean attitude percent score for concepts related to BF was 76.9±7.91. Conclusion: Media and internet have minor roles in getting knowledge about BF. The mean knowledge score about advantages of BF, guidelines of BF and attitude towards BF of all female medical students; especially academic years were unsatisfactory.